The Influence of Education on the Ability to Prepare Digital-Based Financial Statements - Muharram, Andi Iswan; Bustang, Bustang (Phinisi Applied Accounting Journal, 2025)
The advancement of digital technology has impacted various aspects of accounting, including financial reporting processes that now rely on digital systems. This study aims to analyze the influence of education on students' ability to prepare digital-based financial reports. Using a quantitative approach, data was collected through questionnaires distributed to 57 final-year accounting students who had received education in both accounting and information technology. Regression analysis results indicate that education has a positive and significant effect on the ability to prepare digital financial reports, with a regression coefficient of 0.2929 and an R2 value of 0.329. This suggests that educational improvement contributes 32.9% to the enhancement of students' digital competencies. These findings highlight that education integrating information technology into the accounting curriculum can improve students' competencies in meeting the demands of digitalization in the workplace. This study offers valuable insights into advancing accounting education to better adapt to the digital era